Implementasi metode keteladanan guru dalam pembelajaran pendidikan agama islam di SMP Negeri 2 Gemolong - Ngatmin Abbas; Mulyanto Abdullah Khoir (At Turots: Jurnal Pendidikan Islam, 2023)
The implementation of the teacher's exemplary method has been applied in the learning of Islamic Religious Education at SMP Negeri 2 Gemolong, Sragen Regency as an alternative to improve the effectiveness of learning. The survey results showed that 69.1% of students stated that teachers always relate Islamic Religious Education with their daily lives. In addition, observations of the teachers showed that they have applied the exemplary method well in Islamic Religious Education learning. The effectiveness of the implementation of this method is also seen from 75% of students who have achieved or exceeded the minimum completeness criteria set by the school. In this case, the exemplary method can be used as an alternative to improve the effectiveness of Islamic Religious Education learning in schools. In addition, SMP Negeri 2 Gemolong can also be used as a pilot project for strengthening students' characters..